Security dilemmas of the Baltic region - Antczak, Anna; Śliwa, Zdzisław (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2018)
The aim of the paper is to provide an analysis of security in the Baltic region, regarding the decision taken by NATO toward strengthening the security of the Baltic region when facing the threat from the East. It looks deeper into geostrategy as one of the keys to understand the vagaries of security dilemmas in the Baltic area. The article presents a situation analysis from both the Baltic states’ and NATO’s perspectives, having as a background recent actions undertaken by Russia.